Economic Valuation of Pineapple Cultivation on Peat Soil at the Integrated Agricultural Development Area, Samarahan, Sarawak - Daud, Adrian (2009)
Agricultural activities on peat soil are quite common in Malaysia. There are about 2.4 million hectare of peat in the country with 60% of this is located in Sarawak. Pineapple has been traditionally cultivated on peat soil in Malaysia as is the case in Samarahan, Sarawak. The economic value of pineapple cultivation on peat soil should measure beyond private benefits (profit) and include global/social benefits (carbon sequestration value and willingness-to-pay value for better environment). Farmers surrounding the Integrated Agricultural Development Area (IADA) prefer to plant pineapple by using traditional method which means they are not maximizing their returns by planting at a much lower density than recommended by IADA. The high cost in fertilizer associated with pineapple cultivation caused some farmers to resort to plant at a lower density. The returns of the farmers are compared to the potential return with the matrix system (high-density planting). These farmers are also using the traditional method of residue burning which is harmful to the environment. There is a need to emphasize on the proper management of our resources like the sustainable utilization of natural resources such as peat soil. The practice of zero burning technique (ZBT) in pineapple cultivation has the advantage of greater carbon sequestration in soil compared to the traditional practice of residue burning and this the indirect benefit of using ZBT. The value of using ZBT is compared to residue burning technique in terms of net present value (NPV) by using costbenefit analysis (CBA). The total economic value (TEV) is the sum of the private benefits and global/social benefits. There is the incentive to adopt ZBT as it gives higher value than residue burning technique. Farmers who switch to ZBT may experience lower profitability (private benefits) but it results in higher global/social benefits especially through the value of soil carbon sequestration. In the long run it is environmentally sound as it results in the sustainable use of natural resources. The benefit of soil carbon sequestration can compensate the extra cost associated with ZBT. The market price of carbon should be at least RM6.72/tC for ZBT to yield similar total benefits with residue burning technique. The total economic value (TEV) shows that ZBT offers greater net benefit than residue burning. Adopting sustainable practices such as ZBT in our agricultural system is a good step in the utilization of natural resource and should be practiced extensively.